Surface modification of nanoclay for the synthesis of polycaprolactone (PCL)-clay nanocomposite - Kamal, Yusoh; Shamini Vesaya, Kumaran; Fadwa Sameeha, Ismail (EDP Sciences, 2018)
This paper presents a new modification method to modify the surface of nanoclay (Na-MMT) to increase its d-spacing using Aminopropylisooctyl Polyhedral Oligomeric Silsesquioxane (AP-POSS) and the fabrication of Polycaprolactone (PCL) nanocomposite through solution intercalation technique. The structure and morphology of pure nanoclay, modified nanoclay (POSS-MMT) and the PCL nanocomposite were characterized by X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Field Emission Scanning Electron Microscopy (FESEM). XRD revealed that the d-spacing of the POSS-MMT is increased by 0.64 nm as compared to pure nanoclay. FTIR and FESEM results also showed that AP-POSS were well dispersed and intercalated throughout the interlayer space of Na-MMT. An exfoliated structure was also observed for PCL/POSS-MMT nanocomposite. Thermal properties of the nanocomposite were investigated using Thermal Gravimetry Analysis (TGA) which recorded highest degradation temperature for PCL/POSS-MMT 1% nanocomposite which is 394.1°C at 50% weight loss (T50%) but a decrease in degradation temperature when POSS-MMT content is increased and Differential Scanning Calorimetry (DSC) analysis which showed highest melting and crystallization temperature for PCL/POSS-MMT 5% nanocomposite which is 56.6°C and 32.7°C respectively whereas a decrease in degree of crystallinity for PCL/POSS-MMT nanocomposite as compared to PCL/Na-MMT nanocomposite. This study affords an efficient modification method to obtain organoclay with larger interlayer d-spacing to enhance the properties of polymer nanocomposite.